DIFFERENCE LEVEL ON TODDLER DEVELOPMENT AGED 3-4 YEARS Early Childhood Education (ECD) AND NON-ECD IN PUCANGSEWU VILAGE, PACITAN, EAST JAVA - Novian Mahayu Adiutama; Sri Sayekti; Bambang Tutuko (STIKES Insan Cendekia Medika Jombang, 2011)
The toddler should have appropriate stimulation and directed in order to achieve an optimal growth. Stimulation of targeted and appropriate for young children (toddlers) are included on the principles of early childhood education programs, so that early childhood education is very helpful in shaping the structure of a child's development. The purpose of this study was to analyze differences in the growth level of toddler’s development aged 3-4 years ECD and non-ECD in Pucangsewu, Pacitan, East Java. This study used a comparative design with cross sectional approach, the population was toddler aged 3-4 years in the Village Pucangsewu as many as 65, a sample of 56 toddlers were taken by using proportional random sampling technique. Measuring instruments used were DDST II. The data wasanalyzed by using the Mann-Whitney test statistic at 5% error level (α = 0.05). Based on the survey results revealed that the level of development of toddler aged 3-4 years which followed the Early Childhood Education program almost entirely in the normal category (86.9%), little bit was suspect (30,3%) and nobody was in unstable category. Level of toddler’s development aged 3-4 years who did not follow ECD mostly (60,6%) was in suspect category, (30,3%) was normal and (9,1%) was in unstable category. Results of Mann-Whitney test howed p = 0.000 (p <α) so H1 accepted. The results of this study can be concluded that there are differences in the level of development of toddler aged 3-4 years ECD and non-ECD in village Pucangsewu, Pacitan, East Java